Preference of Non-pharmaceutical Preoperative Anxiety Reduction Intervention in Patients Undergoing Elective Surgery - Dagona, Sabo Saleh; Dagona, Sabo Saleh; Archibong, Uduak; McClelland, Gabrielle Tracy (Advances in Social Sciences Research Journal, 2018)
Abstract: For patients to be treated, decisions about their care must be made before treatment begins. In case of pre-operative anxiety, it is currently unknown how clinicians and patients discuss information about the issue, and it is also not known whether clinicians consider (or are ready to consider) their patients’ preferences of non-pharmaceutical pre-operative anxiety reduction interventions. At present no study has been conducted to find information on surgical patients’ preferences of, and their involvement in decisions about non-pharmaceutical interventions for reducing their pre-operative anxiety. This paper investigates elective surgical patients’ involvement in treatment decisions with the aim of finding out their preferred non-pharmaceutical pre-operative anxiety reduction interventions before they undergo elective surgery. Method: A survey method was used to collect data on patients’ preference of non-pharmaceutical preoperative anxiety reduction interventions at a tertiary health facility in Nigeria. Participants: A sample of 30 participants-17 male and 13 female, schedule to undergo surgical operations was selected using a convenient sampling method. Their ages range between 17 to 70 years (mean age = 41.03 and standard deviation = 16.09). Study design/procedure: To elicit preference of interventions, the study participants were presented with cards that contain picture of surgical patient receiving one of the non-pharmaceutical interventions used in reducing pre-operative anxiety. The pictures were presented one at a time for 30-40 seconds. The researcher then gives the participants a sheet of paper with the different interventions boldly written for the participants to rank order them according to the degree of their preferences. Through this process, data was collected from all the 30 participants. Results: The results obtained were entered into SPSS for analysis. Descriptive statistics, at 95 % confidence was calculated to estimate the percentage, mean, standard deviation and confidence intervals based on the participants’ preference of the interventions. Discussions: The findings were discussed alongside the existing literature and recommendations were offered for clinical practice and further research.